Asphalt-based porous carbon material, preparation method thereof and sodium ion battery

Through specific treatment methods of low-temperature asphalt and carbon nanotubes, asphalt-based porous carbon materials with small pores and excellent electrochemical performance were prepared, which solved the problem of asphalt-based porous carbon materials forming large pores during high-temperature carbonization in the prior art, and significantly improved the performance of sodium ion batteries.

CN119822354APending Publication Date: 2025-04-15广东一纳科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411927399.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing asphalt-based porous carbon materials are prone to form large pores during high-temperature carbonization, resulting in poor electrochemical performance and mechanical strength of sodium ion batteries.

Method used

By obtaining low-temperature asphalt and carbon nanotubes, mixing, preoxidizing and heating carbonization, the temperature rise rate is controlled to 1℃/min~10℃/min, the temperature is raised to 600℃~1300℃ and constant temperature treatment for 2h~5h, to prepare asphalt-based porous carbon materials with small porosity and relatively low porosity.

Benefits of technology

The asphalt-based porous carbon material has small porosity, relatively low porosity and good pore uniformity, which improves the specific capacity, rate performance, first-time Coulomb efficiency, mechanical strength and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822354A_ABST
    Figure CN119822354A_ABST
Patent Text Reader

Abstract

The invention provides an asphalt-based porous carbon material, a preparation method thereof and a sodium ion battery. The preparation method of the asphalt-based porous carbon material comprises the following steps: obtaining low-temperature asphalt and carbon nanotubes; mixing the low-temperature asphalt and the carbon nanotubes to obtain a composite material; performing pre-oxidation operation on the composite material to obtain a pre-oxidized material; the pre-oxidized material is subjected to heating type carbonization treatment, the heating rate is 1-10 DEG C, the temperature is increased to 600-1300 DEG C, constant-temperature treatment is conducted for 2-5 h, and the asphalt-based porous carbon material is obtained. According to the preparation method of the asphalt-based porous carbon material, the asphalt-based porous carbon material with relatively small pores, relatively low porosity and relatively good pore uniformity can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an asphalt-based porous carbon material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Asphalt has the advantages of wide sources and low cost, but when used in the negative electrode of sodium ion batteries, it has the disadvantages of low capacity and poor rate performance; carbon nanotubes are a carbon material with excellent performance, and are often added to the electrode slurry as a conductive agent to improve conductivity. Therefore, there are many asphalt and carbon nanotubes that are composited to form asphalt-based porous carbon materials for use in the negative electrode of sodium ion batteries. For example, the invention patent with application number CN202310764630.5 discloses a hard carbon negative electrode material with a multi-layer core-shell structure for sodium ion batteries, which makes the carbon nanotubes uniformly interspersed in the hard carbon, and the diameter of the carbon nanotubes is not more than 20nm;

[0003] It is worth noting that in the preparation process of asphalt-based porous carbon materials, the asphalt needs to be dispersed and carbonized at high temperature. For example, the invention patent application with application number CN202410628593.X discloses a high-performance asphalt-based porous carbon material and a preparation method thereof. In the preparation process of asphalt-based porous carbon materials, the asphalt needs to be dispersed and carbonized at high temperature. In this process, the asphalt is easily mixed with air at high temperature to foam. Although it is mentioned that the added carbon nanotubes can alleviate the problem of asphalt foaming at high temperature, in fact, when the asphalt is carbonized at high temperature, the gas formed by its own decomposition combines with the mixed air, which still causes the asphalt-based porous carbon material to have larger pores and higher porosity.

[0004] However, the porosity of asphalt-based porous carbon materials has a significant influence on the electrochemical performance of sodium-ion batteries. Specifically, the porosity directly determines the specific surface area and the number of sodium ion diffusion channels of the asphalt-based porous carbon materials, that is, it has an impact on the battery rate performance and first coulombic efficiency of the asphalt-based porous carbon materials. In addition, too high a porosity may also cause the material structure to become loose, reducing its mechanical strength and cycle stability. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a pitch-based porous carbon material and a preparation method thereof, and a sodium ion battery with smaller pores, relatively lower porosity, and better pore uniformity, thereby ensuring the battery specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a pitch-based porous carbon material comprises the following steps:

[0008] Get cryogenic pitch and carbon nanotubes;

[0009] Mixing the low-temperature asphalt and the carbon nanotubes to obtain a composite material;

[0010] Performing a pre-oxidation operation on the composite material to obtain a pre-oxidized material;

[0011] The pre-oxidized material is subjected to a temperature-increasing carbonization treatment at a heating rate of 1°C / min to 10°C / min, the temperature is increased to 600°C to 1300°C, and the temperature is kept constant for 2h to 5h to obtain a pitch-based porous carbon material.

[0012] In one of the embodiments, the particle size D50 of the low-temperature asphalt is ≤30 μm.

[0013] In one embodiment, the length of the carbon nanotubes is 1 to 2 times the particle size D50 of the low-temperature asphalt.

[0014] In one embodiment, obtaining low-temperature asphalt includes the following steps:

[0015] The low-temperature asphalt is crushed so that the particle size of the low-temperature asphalt is ≤75 μm;

[0016] The low-temperature asphalt after the crushing process is refined so that the particle size D50 of the low-temperature asphalt is ≤30 μm.

[0017] In one embodiment, before the step of mixing the low-temperature asphalt and the carbon nanotubes and after the step of obtaining the low-temperature asphalt and the carbon nanotubes, the method for preparing the asphalt-based porous carbon material further comprises the following steps:

[0018] The low-temperature asphalt is purified by immersing and cleaning the low-temperature asphalt with an acid solution and an alkaline solution respectively.

[0019] In one embodiment, the acidic solution is at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid.

[0020] In one embodiment, the alkaline solution is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.

[0021] In one embodiment, the mixing operation of the low-temperature asphalt and the carbon nanotubes comprises the following steps:

[0022] Dispersing the low-temperature asphalt to obtain an asphalt treatment liquid;

[0023] The carbon nanotubes are added into the asphalt treatment liquid and subjected to stirring and drying treatment so that the carbon nanotubes are dispersed in the asphalt treatment liquid, and the asphalt treatment liquid is dried.

[0024] In one embodiment, the low-temperature asphalt is dispersed using a solvent;

[0025] The solvent is at least one of n-hexane, carbon disulfide and DMSO.

[0026] In one embodiment, the composite material is pre-oxidized at a temperature of 200°C to 300°C.

[0027] A pitch-based porous carbon material is prepared by the method for preparing a pitch-based porous carbon material described in any of the above embodiments.

[0028] A sodium ion battery comprises a negative electrode sheet, a separator and a positive electrode sheet, wherein the negative electrode sheet, the separator and the positive electrode sheet are stacked, the negative electrode sheet comprises a foil and a negative electrode slurry coated on at least one side of the foil, and the negative electrode slurry contains at least the asphalt-based porous carbon material described in any of the above-mentioned embodiments.

[0029] Compared with the prior art, the present invention has at least the following advantages:

[0030] The preparation method of the asphalt-based porous carbon material of the present invention ensures uniform dispersion of the carbon nanotubes in the low-temperature asphalt during pre-oxidation and carbonization by mixing the low-temperature asphalt and the carbon nanotubes. In the pre-oxidation operation of the composite material, the oxygen atoms can be cross-linked with the low-temperature asphalt molecules to inhibit the molecular rearrangement thereof, so that the interior of the composite material has more disordered sodium storage active space to avoid the graphitization of the low-temperature asphalt causing a decrease in the specific capacity of the battery. In the temperature-raising carbonization treatment of the pre-oxidized material, the temperature is raised at a heating rate of 1°C / min to 10°C / min at room temperature, so that the low-temperature asphalt slowly begins to form gas and discharge it outward during the entire heating process. That is, during the entire heating carbonization process of the low-temperature asphalt, the gas generated by its own cracking is gradually discharged in small quantities during the entire heating process. Further combined with carbon nanotubes, the formation of large pores in the asphalt-based porous carbon material is effectively avoided, that is, the pore size of the pores of the asphalt-based porous carbon material is effectively reduced, and the pore size uniformity of the asphalt-based porous carbon material is improved. After the temperature is raised to 600℃~1300℃ and then treated at a constant temperature for 2h~5h, the sufficient carbonization of the low-temperature asphalt is effectively ensured. In other words, the asphalt-based porous carbon material obtained has smaller pores, relatively lower porosity, and better pore uniformity, thereby improving the battery specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 A flow chart of a method for preparing a pitch-based porous carbon material according to an embodiment of the present invention;

[0033] Figure 2 This is a SEM image of the asphalt-based porous carbon material of Example 12 of the present invention;

[0034] Figure 3 This is a TEM image of the pitch-based porous carbon material of Example 12 of the present invention;

[0035] Figure 4 This is a diagram of the micropore size distribution of the asphalt-based porous carbon material of Example 12 of the present invention. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0037] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0039] The present application provides a method for preparing a pitch-based porous carbon material. The method for preparing the pitch-based porous carbon material comprises the following steps: obtaining low-temperature pitch and carbon nanotubes; mixing the low-temperature pitch and the carbon nanotubes to obtain a composite material; pre-oxidizing the composite material to obtain a pre-oxidized material; performing a temperature-increasing carbonization treatment on the pre-oxidized material at a heating rate of 1°C to 10°C, heating to a temperature of 600°C to 1300°C, and treating at a constant temperature for 2h to 5h to obtain a pitch-based porous carbon material.

[0040] The above-mentioned preparation method of asphalt-based porous carbon material ensures the uniform dispersion of carbon nanotubes in low-temperature asphalt during pre-oxidation and carbonization by mixing the low-temperature asphalt and the carbon nanotubes. In the pre-oxidation operation of the composite material, oxygen atoms can be cross-linked with low-temperature asphalt molecules to inhibit its molecular rearrangement, so that there are more disordered sodium storage active spaces inside, so as to avoid the graphitization of low-temperature asphalt causing a decrease in battery specific capacity. In the temperature-raising carbonization treatment of the pre-oxidized material, the temperature is raised at a heating rate of 1°C / min to 10°C / min at room temperature. In this way, the low-temperature asphalt slowly begins to form gas and discharge it outward during the entire heating process, that is, During the entire heating and carbonization process of the low-temperature asphalt, the gas produced by its own cracking is gradually discharged in small quantities during the entire heating process. Further combined with carbon nanotubes, the formation of large pores in the asphalt-based porous carbon material is effectively avoided, that is, the pore size of the pores of the asphalt-based porous carbon material is effectively reduced, and the pore size uniformity of the asphalt-based porous carbon material is improved. After the temperature is raised to 600℃~1300℃ and then treated at a constant temperature for 2h~5h, the sufficient carbonization of the low-temperature asphalt is effectively ensured. In other words, the asphalt-based porous carbon material has smaller pores, relatively lower porosity, and better pore uniformity, thereby improving the battery specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability.

[0041] In order to better understand the preparation method of the pitch-based porous carbon material of the present application, the preparation method of the pitch-based porous carbon material of the present application is further explained as follows:

[0042] A method for preparing a pitch-based porous carbon material according to one embodiment comprises the following steps:

[0043] S100, obtaining low-temperature asphalt and carbon nanotubes. It can be understood that the low-temperature asphalt has good fluidity during the heating process, and has good strain capacity and flexibility, so that the surface morphology of the low-temperature asphalt is uniform during the heating process; carbon nanotubes have good conductivity, so that carbon nanotubes and low-temperature asphalt are used together as negative electrode materials for sodium ion batteries, and the rate performance and first coulomb efficiency of sodium ion batteries are well achieved.

[0044] S200, mixing the low temperature asphalt and the carbon nanotubes to obtain a composite material. It can be understood that mixing the low temperature asphalt and the carbon nanotubes until they are uniformly dispersed is beneficial to the uniformity of the dispersion of the carbon nanotubes in the product formed during subsequent pre-oxidation and carbonization.

[0045] S300, pre-oxidizing the composite material to obtain a pre-oxidized material. It can be understood that, due to the low softening point of low-temperature asphalt and the fact that it is more likely to rearrange at high temperatures, the surface structure is more ordered, and the pores are relatively small after carbonization to a certain extent, but it will cause graphitization, that is, the carbon formed by carbonization is more converted into an ordered graphite crystalline structure, and the distance between graphite layers gradually becomes smaller, which in turn affects the sodium storage active space of the carbon structure after carbonization, thereby affecting the conduction of sodium ions, and significantly affecting the specific capacity and cycle life of the sodium ion battery. Therefore, the present application first pre-oxidizes the composite material so that the oxygen atoms can cross-link with the low-temperature asphalt molecules, inhibiting its molecular rearrangement, so that it has more disordered sodium storage active space inside, so as to avoid the graphitization of the low-temperature asphalt causing a decrease in the specific capacity of the battery.

[0046] S400, subjecting the pre-oxidized material to a temperature-raising carbonization treatment, with a heating rate of 1°C / min to 10°C / min, heating to a temperature of 600°C to 1300°C, and treating at a constant temperature for 2h to 5h, to obtain a pitch-based porous carbon material. It can be understood that, on the basis of pre-oxidation, the temperature is raised at a heating rate of 1°C / min to 10°C / min at room temperature, so that the low-temperature asphalt slowly begins to form gas and discharges outward during the entire heating process, that is, during the entire heating and carbonization process of the low-temperature asphalt, the gas generated by its own cracking is gradually discharged in small quantities during the entire heating process, and further with carbon nanotubes, the formation of large pores in the pitch-based porous carbon material is effectively avoided, that is, the pore size of the pores of the pitch-based porous carbon material is effectively reduced, and the pore size uniformity of the pitch-based porous carbon material is better, and the temperature is raised to 600°C to 1300°C and then treated at a constant temperature for 2h to 5h, which effectively ensures the full carbonization of the low-temperature asphalt.

[0047] The above-mentioned preparation method of asphalt-based porous carbon material ensures the uniform dispersion of carbon nanotubes in low-temperature asphalt during pre-oxidation and carbonization by mixing the low-temperature asphalt and the carbon nanotubes. In the pre-oxidation operation of the composite material, oxygen atoms can be cross-linked with low-temperature asphalt molecules to inhibit its molecular rearrangement, so that there are more disordered sodium storage active spaces inside, so as to avoid the graphitization of low-temperature asphalt causing a decrease in battery specific capacity. In the temperature-raising carbonization treatment of the pre-oxidized material, the temperature is raised at a heating rate of 1°C / min to 10°C / min at room temperature. In this way, the low-temperature asphalt slowly begins to form gas and discharge it outward during the entire heating process, that is, During the entire heating and carbonization process of the low-temperature asphalt, the gas produced by its own cracking is gradually discharged in small quantities during the entire heating process. Further combined with carbon nanotubes, the formation of large pores in the asphalt-based porous carbon material is effectively avoided, that is, the pore size of the pores of the asphalt-based porous carbon material is effectively reduced, and the pore size uniformity of the asphalt-based porous carbon material is improved. After the temperature is raised to 600℃~1300℃ and then treated at a constant temperature for 2h~5h, the sufficient carbonization of the low-temperature asphalt is effectively ensured. In other words, the asphalt-based porous carbon material has smaller pores, relatively lower porosity, and better pore uniformity, thereby improving the battery specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability.

[0048] It should be noted that since low-temperature asphalt is more easily graphitized due to high-temperature carbonization, it is necessary to increase pre-oxidation to allow oxygen atoms to act on carbon atoms, and further cooperate with carbon nanotubes to allow oxygen atoms to act more fully on carbon atoms, effectively inhibiting the rearrangement of carbon atoms and making it have more disordered sodium storage active space inside. However, only through sufficient pre-oxidation of low-temperature asphalt and its own good fluidity, and then cooperate with carbon nanotubes to better reduce the generation of foaming. But in fact, since low-temperature asphalt still has viscosity, and when it is cracked at high temperature, the gas formed by its own cracking Rapid formation will still cause the pores of the asphalt-based porous carbon material to be larger, and it is difficult to ensure the uniformity of the pores. Therefore, in the present application, low-temperature asphalt is selected, and the heating rate is controlled to be 1°C / min~10°C / min, and the temperature is raised to 600°C~1300°C, so that it slowly begins to form gas and discharge it to the outside during the entire heating process, avoiding the rapid and large-scale formation of bubbles during asphalt cracking, that is, achieving effective control of the speed and amount of gas generated by asphalt cracking, and then achieving the preparation of asphalt-based porous carbon materials with smaller pores, relatively low porosity, and better pore uniformity.

[0049] It should also be noted that the purpose of selecting low-temperature asphalt is that it can achieve the formation of gas from its own cracking at a relatively low temperature. The heating rate is 1°C / min to 10°C / min, which avoids the rapid and large-scale formation of bubbles during asphalt cracking. That is, during the entire heating process of the low-temperature asphalt, the speed and amount of gas produced by asphalt cracking are controlled, so that the asphalt cracks smoothly and releases a small amount of gas gradually and evenly, thereby better ensuring the reduction of the pore size of the pores in the asphalt-based porous carbon material and improving the pore size uniformity of the asphalt-based porous carbon material.

[0050] It should also be noted that if other types of asphalt are selected, such as high-temperature asphalt and coal tar pitch, they need to be effectively cracked at a higher temperature to evenly produce gas. At higher temperatures, the speed and amount of gas produced by the cracking of coal tar asphalt and high-temperature asphalt are more difficult to control. Therefore, the present application selects low-temperature asphalt and carbon nanotubes in combination with gradient heating, from room temperature at a heating rate of 1°C / min to 10°C / min to a temperature of 600°C to 1300°C, which effectively achieves the smooth cracking of the asphalt and gradually and evenly releases a small amount of gas, thereby better ensuring the reduction of the pore size of the pores of the asphalt-based porous carbon material and improving the pore size uniformity of the asphalt-based porous carbon material.

[0051] It can be understood that since low-temperature asphalt mainly contains polycyclic short-chain aromatic hydrocarbons, a small amount of aliphatic hydrocarbons, colloids and asphaltenes, when the heating rate is 1°C / min to 10°C / min, the gas generation rate and amount of low-temperature asphalt can be effectively achieved. However, because the various types of substances contained in the low-temperature asphalt have different compositions and contents, when it is heated to 600°C to 1300°C at a single heating rate, the gas generation rate and amount in different heating time periods have large fluctuations. In order to better ensure the reduction of the pore size of the asphalt-based porous carbon material and the improvement of the pore size uniformity of the asphalt-based porous carbon material, in one embodiment, the pre-oxidized material is subjected to a temperature-increasing carbonization treatment, comprising the following steps:

[0052] The pre-oxidized material is subjected to a heating treatment at a heating rate of 5°C / min to 10°C / min, and the temperature is raised to 200°C to 250°C;

[0053] The pre-oxidized material is subjected to a two-stage heating treatment at a heating rate of 3°C / min to 5°C / min, and the temperature is raised to 400°C to 500°C;

[0054] The pre-oxidized material is subjected to a two-stage heating treatment at a heating rate of 1°C / min to 2°C / min, and the temperature is raised to 600°C to 1300°C;

[0055] The pre-oxidation is subjected to a constant temperature treatment for 2 h to 5 h.

[0056] It can be understood that the pre-oxidized material is subjected to a first-stage temperature increase treatment at a heating rate of 5°C / min to 10°C / min, and the temperature is increased to 200°C to 250°C, which ensures the generation rate and amount of gas at this stage, and promotes that the amount of bubbles formed when the gas is released from the pre-oxidized material is large and the radius is small, thereby ensuring that the pores of the asphalt-based porous carbon material are small, the porosity is relatively low, and the pore uniformity is good; further, the pre-oxidized material is subjected to a second-stage temperature increase treatment at a heating rate of 3°C / min to 5°C / min, and the temperature is increased to 400°C to 500°C, which further ensures the generation rate and amount of gas at this stage, and promotes that the amount of bubbles formed when the gas is released from the pre-oxidized material is large and the radius is small, This further ensures that the pores of the asphalt-based porous carbon material are small, the porosity is relatively low, and the pore uniformity is good. Furthermore, the pre-oxidized material is subjected to a two-stage temperature increase treatment at a heating rate of 1°C / min to 2°C / min, and the temperature is increased to 600°C to 1300°C, thereby ensuring the gas generation rate and amount at this stage, and promoting the formation of bubbles with a large amount and a small radius when the gas is released from the pre-oxidized material, thereby further ensuring that the pores of the asphalt-based porous carbon material are small, the porosity is relatively low, and the pore uniformity is good. Furthermore, the pre-oxidation is subjected to a constant temperature treatment for 2h to 5h, at which time the content of low-temperature asphalt is small, and further constant temperature treatment can ensure sufficient cracking and carbonization of the low-temperature asphalt.

[0057] In one embodiment, the particle size D50 of the low-temperature asphalt is ≤30μm. Furthermore, the tube length of the carbon nanotube is 1 to 2 times the particle size D50 of the low-temperature asphalt. It can be understood that, assuming the particle size D50 of the low-temperature asphalt is x, and the tube length of the carbon nanotube is y, then x≤y≤2x. Furthermore, the mass ratio of the low-temperature asphalt to the carbon nanotube is (180~210):1. It can be understood that the carbon nanotube forms an embedded doping state in the asphalt, that is, the carbon nanotube is embedded in the asphalt.

[0058] It should be noted that if the qualities of low-temperature asphalt and carbon nanotubes are relatively high or low, and the particle size of low-temperature asphalt and the length of carbon nanotubes are relatively high or low, the state of carbon nanotubes embedded in low-temperature asphalt cannot be formed, and the carbon nanotubes are embedded in the low-temperature asphalt, which effectively ensures the sufficient pre-oxidation of the low-temperature asphalt, and effectively increases the number and uniformity of bubbles formed by gas release during high-temperature cracking and carbonization of low-temperature asphalt, thereby better ensuring that the pores of the asphalt-based porous carbon material are small, the porosity is relatively low, and the pore uniformity is good.

[0059] In one embodiment, obtaining low-temperature asphalt includes the following steps:

[0060] The low temperature asphalt is crushed so that the particle size of the low temperature asphalt is ≤75 μm. Further, the particle size of the low temperature asphalt is 50 μm to 75 μm. Further, the low temperature asphalt is crushed by a roller crushing method.

[0061] Furthermore, the low-temperature asphalt after the crushing process is refined so that the particle size D50 of the low-temperature asphalt is ≤30μm. Furthermore, the particle size D50 of the low-temperature asphalt is 8μm to 30μm. Furthermore, the low-temperature asphalt is refined by air flow crushing or ball milling, which better improves the uniformity and efficiency of the particle size refinement of the low-temperature asphalt.

[0062] In one embodiment, before the step of mixing the low-temperature asphalt and the carbon nanotubes and after the step of obtaining the low-temperature asphalt and the carbon nanotubes, the method for preparing the asphalt-based porous carbon material further comprises the following steps:

[0063] The low-temperature asphalt is purified by immersing and cleaning the low-temperature asphalt with an acid solution and an alkaline solution respectively.

[0064] In one embodiment, the acidic solution is at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid. Further, the concentration of the acidic solution is 2 mol / L to 8 mol / L.

[0065] In one embodiment, the alkaline solution is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide. Further, the concentration of the alkaline solution is 2 mol / L to 8 mol / L.

[0066] In one embodiment, the low-temperature asphalt is purified, and the specific steps are: adding the low-temperature asphalt to an acidic solution for a first stirring, adding it to an alkaline solution for a second stirring after suction filtration, washing it with deionized water until the pH is 6.8 to 7.2 after suction filtration, and drying it. Further, the first stirring is stirring at room temperature for 2h to 10h. Further, the speed of the first stirring is 100r / min to 800r / min. Further, the second stirring is stirring at room temperature for 2h to 10h. Further, the speed of the second stirring is 100r / min to 800r / min. Further, the drying temperature is 80℃ to 100℃. Further, the drying time is 2h to 10h.

[0067] It can be understood that the use of acidic solution to impregnate and stir the low-temperature asphalt effectively achieves the removal of metal elements such as aluminum and iron in the low-temperature asphalt, and the subsequent use of alkaline solution to clean the low-temperature asphalt effectively achieves the removal of silicon in the low-temperature asphalt and better ensures the effective regulation of the pH of the low-temperature asphalt.

[0068] In one embodiment, the mixing operation of the low-temperature asphalt and the carbon nanotubes comprises the following steps:

[0069] Dispersing the low-temperature asphalt to obtain an asphalt treatment liquid;

[0070] The carbon nanotubes are added into the asphalt treatment liquid and subjected to stirring and drying treatment so that the carbon nanotubes are dispersed in the asphalt treatment liquid, and the asphalt treatment liquid is dried.

[0071] In one embodiment, the low-temperature asphalt is dispersed by a solvent. Further, the solvent is at least one of n-hexane, carbon disulfide and DMSO. Further, the low-temperature asphalt is dispersed by a solvent, and the specific operation is: adding the low-temperature asphalt to the solvent for mixing and stirring, and heating to 40°C to 60°C at the same time. Further, the mixing and stirring speed is 100r / min to 800r / min. Further, the mixing and stirring time is 2h to 5h, which better ensures the full dispersion of the low-temperature asphalt, and further better ensures the full dispersion of the carbon nanotubes in the low-temperature asphalt.

[0072] In one embodiment, the carbon nanotubes are added to the asphalt treatment liquid for stirring and drying, and the stirring speed is 100 r / min to 800 r / min and the stirring time is 2 h to 5 h.

[0073] In one embodiment, drying the asphalt treatment fluid comprises the following steps:

[0074] performing a preliminary drying treatment on the asphalt treatment fluid;

[0075] The asphalt treatment liquid that has undergone preliminary drying treatment is subjected to deep drying treatment.

[0076] In one embodiment, the asphalt treatment liquid is subjected to a preliminary drying treatment at a drying temperature of 60° C. to 90° C. Furthermore, the drying time is 5 h to 10 h.

[0077] In one embodiment, the asphalt treatment liquid subjected to the preliminary drying treatment is subjected to a deep drying treatment at a drying temperature of 80° C. to 150° C. Further, the drying time is 1 hour to 10 hours. Further, the asphalt treatment liquid subjected to the preliminary drying treatment is placed in a blast drying oven for a deep drying treatment.

[0078] In one embodiment, the composite material is pre-oxidized at a temperature of 200°C to 300°C. Further, the pre-oxidation operation time is 1h to 5h. It can be understood that the mass ratio of carbon nanotubes to low-temperature asphalt, and the ratio of the particle size of low-temperature asphalt to the length of carbon nanotubes are matched, so that it is oxidized at a temperature of 200°C to 300°C for 1h to 5h, which effectively ensures the full oxidation of low-temperature asphalt.

[0079] In one embodiment, after the step of subjecting the pre-oxidized material to a temperature-raising carbonization treatment, the method for preparing the asphalt-based porous carbon material further comprises the following steps: subjecting the asphalt-based porous carbon material to a cooling and refining treatment, so that the particle size D50 of the asphalt-based porous carbon material is 6 μm to 15 μm after the asphalt-based porous carbon material is cooled. Furthermore, the asphalt-based porous carbon material is subjected to a cooling and refining treatment by air flow pulverization or ball milling.

[0080] The present application also provides a pitch-based porous carbon material, which is prepared by the preparation method of the pitch-based porous carbon material described in any of the above embodiments. Further, in this embodiment, the preparation method of the pitch-based porous carbon material includes the following steps: obtaining low-temperature pitch and carbon nanotubes; mixing the low-temperature pitch and the carbon nanotubes to obtain a composite material; pre-oxidizing the composite material to obtain a pre-oxidized material; performing a temperature-increasing carbonization treatment on the pre-oxidized material, with a heating rate of 1°C to 10°C, heating to a temperature of 600°C to 1300°C, and treating at a constant temperature for 2h to 5h to obtain a pitch-based porous carbon material.

[0081] The above-mentioned asphalt-based porous carbon material realizes the preparation of asphalt-based porous carbon material with small pores, relatively low porosity and good pore uniformity.

[0082] The present application also provides a sodium ion battery. A sodium ion battery in one embodiment includes a negative electrode sheet, a separator and a positive electrode sheet, wherein the negative electrode sheet, the separator and the positive electrode sheet are stacked, the negative electrode sheet includes a foil and a negative electrode slurry coated on at least one side of the foil, and the negative electrode slurry contains at least the asphalt-based porous carbon material described in any of the above embodiments.

[0083] The above-mentioned sodium ion battery uses asphalt-based porous carbon material, which effectively improves the battery's specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability.

[0084] Compared with the prior art, the present invention has at least the following advantages:

[0085] The preparation method of the asphalt-based porous carbon material of the present invention ensures uniform dispersion of the carbon nanotubes in the low-temperature asphalt during pre-oxidation and carbonization by mixing the low-temperature asphalt and the carbon nanotubes. In the pre-oxidation operation of the composite material, the oxygen atoms can be cross-linked with the low-temperature asphalt molecules to inhibit the molecular rearrangement thereof, so that the interior of the composite material has more disordered sodium storage active space to avoid the graphitization of the low-temperature asphalt causing a decrease in the specific capacity of the battery. In the temperature-raising carbonization treatment of the pre-oxidized material, the temperature is raised at a heating rate of 1°C / min to 10°C / min at room temperature, so that the low-temperature asphalt slowly begins to form gas and discharge it outward during the entire heating process. That is, during the entire heating carbonization process of the low-temperature asphalt, the gas generated by its own cracking is gradually discharged in small quantities during the entire heating process. Further combined with carbon nanotubes, the formation of large pores in the asphalt-based porous carbon material is effectively avoided, that is, the pore size of the pores of the asphalt-based porous carbon material is effectively reduced, and the pore size uniformity of the asphalt-based porous carbon material is improved. After the temperature is raised to 600℃~1300℃ and then treated at a constant temperature for 2h~5h, the sufficient carbonization of the low-temperature asphalt is effectively ensured. In other words, the asphalt-based porous carbon material obtained has smaller pores, relatively lower porosity, and better pore uniformity, thereby improving the battery specific capacity, rate performance, first coulombic efficiency, mechanical strength and cycle stability.

[0086] Some specific examples are listed below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.

[0087] Example 1

[0088] The blocky low-temperature asphalt was crushed to a particle size of 50 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 8 μm using a jet mill;

[0089] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0090] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0091] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 180:1, and the tube length of the single-walled carbon nanotubes is 1 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0092] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0093] Example 2

[0094] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0095] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0096] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0097] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 180:1, and the tube length of the single-walled carbon nanotubes is 1 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0098] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0099] Example 3

[0100] The blocky low-temperature asphalt was crushed to a particle size of 75 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 30 μm using a jet mill;

[0101] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0102] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0103] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 180:1, and the tube length of the single-walled carbon nanotubes is 1 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0104] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0105] Example 4

[0106] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0107] Add low-temperature asphalt to 3 mol / L nitric acid and stir at room temperature for 10 hours at a stirring speed of 100 r / min. After suction filtration, add the filtrate to 3 mol / L potassium hydroxide and stir at room temperature for 10 hours at a stirring speed of 100 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at 80°C for 10 hours;

[0108] The low-temperature asphalt is added to carbon disulfide and mixed and stirred, and heated to 60° C. at a mixing and stirring speed of 100 r / min for 5 hours to obtain asphalt liquid;

[0109] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 180:1, and the tube length of the single-walled carbon nanotubes is 1 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0110] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0111] Example 5

[0112] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0113] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0114] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0115] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0116] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0117] Example 6

[0118] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0119] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0120] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0121] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 210:1, and the tube length of the single-walled carbon nanotubes is twice the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0122] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0123] Example 7

[0124] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0125] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0126] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0127] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 100 r / min. The stirring time is 5 hours, and the asphalt treatment liquid is dried at a temperature of 60°C for 10 hours, and then the asphalt liquid is placed in a blast drying oven for 10 hours at a drying temperature of 80°C to obtain a dry composite;

[0128] The composite was pre-oxidized in an air atmosphere at a temperature of 300°C for 1 hour, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0129] Example 8

[0130] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0131] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0132] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0133] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0134] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material is then ball-milled to a particle size D50 of 10 μm.

[0135] Example 9

[0136] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0137] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0138] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0139] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0140] The composite was pre-oxidized in an air atmosphere at a temperature of 200°C for 5 hours, and then cooled. The composite was carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0141] Example 10

[0142] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0143] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0144] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0145] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0146] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 5°C / min to a temperature of 1000°C and kept at a constant temperature for 3 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material is then ball-milled to a particle size D50 of 10 μm.

[0147] Embodiment 11

[0148] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0149] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0150] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0151] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0152] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 10°C / min to a temperature of 600°C and kept at a constant temperature for 5 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material is then ball-milled to a particle size D50 of 10 μm.

[0153] Example 12

[0154] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0155] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0156] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0157] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0158] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 5°C / min to a temperature of 200°C, then at a heating rate of 3°C / min to a temperature of 400°C, then at a heating rate of 1°C / min to a temperature of 1300°C. The mixture is treated at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material, and then the asphalt-based porous carbon material is ball-milled to a particle size D50 of 10 μm.

[0159] Example 13

[0160] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0161] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0162] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0163] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0164] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 8°C / min to a temperature of 250°C, then at a heating rate of 5°C / min to a temperature of 500°C, then at a heating rate of 1°C / min to a temperature of 1300°C. The mixture is treated at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material, and then the asphalt-based porous carbon material is ball-milled to a particle size D50 of 10 μm.

[0165] Embodiment 14

[0166] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0167] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0168] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0169] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0170] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 10°C / min to 250°C, then at a heating rate of 5°C / min to 500°C, then at a heating rate of 2°C / min to 1300°C. The mixture is kept at a constant temperature for 2 hours to obtain a pitch-based porous carbon material, and then the particle size D50 of the ball-milled pitch-based porous carbon material is 10 μm.

[0171] Embodiment 15

[0172] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0173] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0174] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0175] The multi-walled carbon nanotubes (the mass ratio of low-temperature asphalt to multi-walled carbon nanotubes is 200:1, and the tube length of the multi-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0176] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 10°C / min to 250°C, then at a heating rate of 5°C / min to 500°C, then at a heating rate of 2°C / min to 1300°C. The mixture is kept at a constant temperature for 2 hours to obtain a pitch-based porous carbon material, and then the particle size D50 of the ball-milled pitch-based porous carbon material is 10 μm.

[0177] Comparative Example 1

[0178] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0179] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0180] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0181] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 3 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0182] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material is then ball-milled to a particle size D50 of 10 μm.

[0183] Comparative Example 2

[0184] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0185] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0186] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0187] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 0.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0188] The composite is pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite is carbonized in an inert atmosphere at a heating rate of 1°C / min to a temperature of 1300°C and kept at a constant temperature for 2 hours to obtain a asphalt-based porous carbon material. The asphalt-based porous carbon material is then ball-milled to a particle size D50 of 10 μm.

[0189] Comparative Example 3

[0190] The blocky low-temperature asphalt was crushed to a particle size of 60 μm using a double-roll mill, and then the crushed LTP was processed to a particle size of D50 = 10 μm using a jet mill;

[0191] Add low-temperature asphalt to 3 mol / L hydrochloric acid solution and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, add the filtrate to 3 mol / L sodium hydroxide and stir at room temperature for 2 hours at a stirring speed of 800 r / min. After suction filtration, wash the filtrate with deionized water until the pH is 7.0, and dry it at a temperature of 100°C for 2 hours;

[0192] The low-temperature asphalt is added to n-hexane and mixed and stirred, and heated to 40° C. at a mixing and stirring speed of 800 r / min for 2 h to obtain asphalt liquid;

[0193] The single-walled carbon nanotubes (the mass ratio of low-temperature asphalt to single-walled carbon nanotubes is 200:1, and the tube length of the single-walled carbon nanotubes is 1.5 times the particle size D50 of the low-temperature asphalt) are added to the asphalt liquid for stirring at a stirring speed of 800r / min. The stirring time is 2h, and the asphalt treatment liquid is dried at a temperature of 90°C for 5h, and then the asphalt liquid is placed in a blast drying oven for 1h at a drying temperature of 150°C to obtain a dry composite;

[0194] The composite was pre-oxidized in an air atmosphere at a temperature of 250°C for 3 hours, and then cooled. The composite was carbonized in an inert atmosphere at a temperature of 1300°C for 3 hours to obtain a pitch-based porous carbon material. The pitch-based porous carbon material was then ball-milled to a particle size D50 of 10 μm.

[0195] The asphalt-based porous carbon materials obtained in Examples 1 to 15 and the asphalt-based porous carbon materials obtained in Comparative Examples 1 to 3 were subjected to structural observation, mechanical property testing, carbonization rate and electrical conductivity testing, and oxygen content testing of the pre-oxidation products. The results are shown in Table 1.

[0196] Table 1

[0197]

[0198]

[0199] The asphalt-based porous carbon materials obtained in Examples 1 to 15 and the asphalt-based porous carbon materials obtained in Comparative Examples 1 to 3 are used to prepare sodium ion batteries (CR2032 button batteries):

[0200] The sodium ion batteries obtained above were subjected to constant current charge and discharge tests at a current density of 0.02 A / g, and the electrochemical properties were recorded. The results are shown in Table 2.

[0201] Table 2

[0202]

[0203]

[0204] Please also read Figure 2 As can be seen from Table 1 and Table 2, the asphalt-based porous carbon material of the embodiment has smaller pores, higher uniformity, and significantly better electrochemical performance than the asphalt-based porous carbon material of the comparative example. Therefore, by controlling the particle size of the low-temperature asphalt and the length of the carbon nanotubes, as well as their ratio, combined with step-by-step temperature carbonization, the preparation of asphalt-based porous carbon materials with small, numerous pores and good uniformity can be effectively achieved, thereby effectively improving the electrochemical performance of the asphalt-based porous carbon materials, especially the asphalt-based porous carbon materials in Examples 12 to 15 are better, and further, Example 12 is particularly optimal.

[0205] From Figure 3 and Figure 4 It can be seen that in the asphalt-based porous carbon material of Example 12, the carbon nanotubes and the low-temperature asphalt hard carbon are uniformly combined and well dispersed, the surface of the composite material is flat and smooth, and there is no obvious open hole structure. TEM shows that the surface of the particles has a graphitized layer and the interior is an amorphous structure, thus taking into account both high first coulomb efficiency and high sodium storage capacity.

[0206] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a pitch-based porous carbon material, characterized in that: The steps include: Get cryogenic pitch and carbon nanotubes; Mixing the low-temperature asphalt and the carbon nanotubes to obtain a composite material; Performing a pre-oxidation operation on the composite material to obtain a pre-oxidized material; The pre-oxidized material is subjected to a temperature-increasing carbonization treatment at a heating rate of 1°C / min to 10°C / min, the temperature is increased to 600°C to 1300°C, and the temperature is kept constant for 2h to 5h to obtain a pitch-based porous carbon material.

2. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: The particle size D50 of the low-temperature asphalt is ≤30 μm; and / or, The tube length of the carbon nanotube is 1 to 2 times the particle size D50 of the low-temperature asphalt.

3. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: Obtaining low-temperature asphalt includes the following steps: The low-temperature asphalt is crushed so that the particle size of the low-temperature asphalt is ≤75 μm; The low-temperature asphalt after the crushing process is refined so that the particle size D50 of the low-temperature asphalt is ≤30 μm.

4. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: Before the step of mixing the low-temperature asphalt and the carbon nanotubes and after the step of obtaining the low-temperature asphalt and the carbon nanotubes, the method for preparing the asphalt-based porous carbon material further comprises the following steps: The low-temperature asphalt is purified by immersing and cleaning the low-temperature asphalt with an acid solution and an alkaline solution respectively.

5. The method for preparing a pitch-based porous carbon material according to claim 4, characterized in that: The acidic solution is at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid; and / or, The alkaline solution is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.

6. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: The low-temperature asphalt and the carbon nanotubes are mixed, comprising the following steps: Dispersing the low-temperature asphalt to obtain an asphalt treatment liquid; The carbon nanotubes are added into the asphalt treatment liquid and subjected to stirring and drying treatment so that the carbon nanotubes are dispersed in the asphalt treatment liquid, and the asphalt treatment liquid is dried.

7. The method for preparing a pitch-based porous carbon material according to claim 6, characterized in that: Using a solvent to disperse the low-temperature asphalt; The solvent is at least one of n-hexane, carbon disulfide and DMSO.

8. The method for preparing a pitch-based porous carbon material according to claim 1, characterized in that: The composite material is subjected to a pre-oxidation operation at a temperature of 200° C. to 300° C.

9. A pitch-based porous carbon material, characterized in that: The method for preparing a pitch-based porous carbon material is used as described in any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: It includes a negative electrode sheet, a separator and a positive electrode sheet, wherein the negative electrode sheet, the separator and the positive electrode sheet are stacked, the negative electrode sheet includes a foil and a negative electrode slurry coated on at least one side of the foil, and the negative electrode slurry contains at least the asphalt-based porous carbon material according to claim 9.

Citation Information

Patent Citations

  • Hard carbon negative electrode material with multi-layer core-shell structure for sodium ion battery and preparation method of hard carbon negative electrode material

    CN117154029A

  • High-performance asphalt-based porous carbon material and preparation method thereof

    CN118206115A